SIMULATED YIELD AND NET RETURN OF A MAIZE CROP FERTILIZED WITH DIFFERENT SOURCES AND RATES OF NITROGEN - ANDRADE, CAMILO DE LELIS TEIXEIRA DE; AMARAL, TALES ANTÔNIO; DUARTE, JASON DE OLIVEIRA; GARCIA, JOÃO CARLOS; SILVA, DENISE DE FREITAS; MARTINS, PAULO CÉZAR (International Journal of Maize & Sorghum, 2013)
The goal of this study was to evaluate yield and net return of a maize crop fertilized with different rates of conventional mineral fertilizer and cattle manure. The CSM-CERES-Maize model was used to simulate the nitrogen (N) fertilization management scenarios. Twelve treatments were simulated as follows: T1, T2 and T3 were, rates of 90, 130 and 160 kg ha-1 of N as conventional fertilizer, respectively; T4a, T4b and T4c were 4.5 t ha-1 of air-dried cattle manure, rated at 17.05, 22.73 and 34.09 US per ton, respectively; T5a, T5b and T5c were 6.5 t ha-1 of air-dried cattle manure, rated at US 17.05, US 22.73 and US 34.09 per ton, respectively; T6a, T6b and T6c were 8.0 t ha-1 of air-dried cattle manure, rated at US 17.05, US 22.73 and US 34.09 US per ton. It was assumed that the air-dried cattle manure has 2% of N. The conventional mineral fertilization with a nitrogen rate of 90 kg ha-1 (T1) resulted in an average yield of 4.812 kg ha-1 and average profitability of US 35.56 ha-1, while higher nitrogen rates caused economic losses. Profitabilities of US 120.90 and US 183.50 ha-1 were obtained with cattle manure rates of 6,500 and 8,000 kg ha-1, respectively.